Computer algebra in scientific computing : 21st International Workshop, CASC 2019, Moscow, Russia, August 26-30, 2019, Proceedings /: 21st International Workshop, CASC 2019, Moscow, Russia, August 26-30, 2019, Proceedings. (2019) - Unknown
No abstract available